Some comments about the psychological views of Eastern thinkers - Layli Khidoyatova (Genius Journals, 2023)
Based on the relevance of education of young people and the formation of their character in a positive way, we found it necessary to reflect on the psychological views of Eastern thinkers. In this article, we focused on the social and psychological factors that cause the formation of the personality, defining the psychological and pedagogical conditions, as well as the ideas and concepts about the spirit. Information was also given about the role of human spirit as a psychological mechanism. The article focused on the philosophical and psychological views of Central Asian thinkers Abu Raikhan Beruni, Abu Nasr Farabi, Ahmed Yassavi, Abu Ali Ibn Sina, Husayn Vaiz Koshifi, Pahlavon Mahmud and others.
Keywords: Psychological views; perfect person; mind